COMPARISON OF CHATTER CONTROL OF VARIABLE AND REGULAR HELIX TOOLS IN THE ALUMINUM END-MILLING PROCESS - Sonief, Achmad As’ad; Ma'arif, Moch. Syamsul; Pratikto, Pratikto; Juliano, Hans (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2023)
In the chatter, machining operations are undesirable because of the phenomena that affect product results, machining accuracy, tool life, and high operating value. Chatter is a vibration phenomenon that occurs in cutting tools due to the self-excitation of the influence of cutting parameters during the operation process of the machine. Types of chatter in machinery are regenerative and resonant. Because the pitch angles of variable helix tools vary, the helix angles of variable tools produce different tooth passing frequencies on each tool eye next to each other and can be used to prevent and control resonance. This study aimed to compare chatter control from the variable helix and regular-angle tools in the aluminum end milling process. The method is carried out through the end milling process experiment to determine the chatter control of the variable helix and regular-angle tools through the stability loop diagram. The results from this study were obtained by comparing control chatters in the milling process through controlling variable and standard helix angles as a guideline to produce the best surface roughness in the end milling process made from aluminum. The comparison of estimated control charts from variable helix tools is more comprehensive than regular helix tools.